Economic Uncertainty and Fertility - Giray Gozgor; Mehmet Huseyin Bilgin; Peter Rangazas (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In this paper, we conduct an empirical study of how uncertainty alters fertility behavior. The precautionary motive for saving predicts that an increase in income uncertainty increases saving by reducing both consumption and fertility. We examine this prediction using a new measure of economic uncertainty, the World Uncertainty Index and focus on data from 126 countries for the period from 1996 to 2017. The empirical findings indicate that uncertainty decreases the fertility rate, as suggested by theory. This evidence is robust to different model specifications and econometric techniques as well as to the inclusion of various controls. The evidence also indicates that changes in uncertainty may be a factor explaining why fertility is pro-cyclical.
Keywords: J13; D81; D14; E32; C33; 330; fertility; uncertainty; WUI Index; precautionary saving; business cycle; panel data estimation techniques